FAKTOR â€“ FAKTOR YANG BERHUBUNGAN DENGAN KEJADIANANEMI PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS SEI LANGKAI KOTA BATAM - Serlinawati, Serlinawati; Sulistyawati, Tri Ribut; Yunita, Prasida (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
A pregnant woman, by the WHO standard, isconsidered anemic if her hemoglobin (Hb) concentration during the gestation is lower than 11 g/dL, or hematocrit of <33% during the period of pregnancy (Sharma and Meenakshi, 2010). This research aims to discover the correlative factors to the prevalence of anemia amongst pregnant women in the coverage area of Puskesmas (community clinic) Sei Langkai, Batam, in 2019. The research design employs analytic descriptive with cross-sectional approach. Data collecting technique employs total sampling with the total sample population of 63 pregnant women.The univariate analysis is in frequency distribution tables, and the bivariate analysis employs the chi-square. The findings reveal correlative factors to the prevalence of anemia amongst pregnant women are as follows, out of 63pregnant women; suffering from mild anemia are 33 (52.4%) respondents, from moderate anemia are 17 (27%) respondents, and from severe anemia are 13 (20.6%) respondents; with full antenatal visits are 40 (63.5%) respondents, non-full antenatal visits are 23 (36.5%) respondents; whose income â‰¥Rp3.8 million are 42 (66.7%) respondents, income <Rp3.8 million are 21 (33.3%) respondents; without any food abstinence are 48 (76.2%) respondents, with certain food abstinence are 15 (23.8%) respondents; the primiparous are 31 (49.2%), the multiparous are 19 (30.2%) respondents, and the grand multiparous are 13 (20.6%) respondents. In conclusion, there are correlations between anemia in pregnant women and their antenatal visits, social economy, social culture, and the status of their parity. In suggestion, the government and stakeholders must take more actions and be more active in spreading information about the causative factors and the risks of anemia in a pregnant woman, so the prevalence rate can be reduced.